Repeat-containing protein effectors of plant-associated organisms - Mesarich, Carl H.; Bowen, Joanna K.; Hamiaux, Cyril; Templeton, Matthew D. (Frontiers in Plant Science, 2015)
Many plant-associated organisms, including microbes, nematodes, and insects, deliver effector proteins into the apoplast, vascular tissue, or cell cytoplasm of their prospective hosts. These effectors function to promote colonization, typically by altering host physiology or by modulating host immune responses. The same effectors however, can also trigger host immunity in the presence of cognate host immune receptor proteins, and thus prevent colonization. To circumvent effector-triggered immunity, or to further enhance host colonization, plant-associated organisms often rely on adaptive effector evolution. In recent years, it has become increasingly apparent that several effectors of plant-associated organisms are repeat-containing proteins (RCPs) that carry tandem or non-tandem arrays of an amino acid sequence or structural motif. In this review, we highlight the diverse roles that these repeat domains play in RCP effector function. We also draw attention to the potential role of these repeat domains in adaptive evolution with regards to RCP effector function and the evasion of effector-triggered immunity. The aim of this review is to increase the profile of RCP effectors from plant-associated organisms.